Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
the sum means x+y=sum
the sum of 2 and 1 is 3
then you subtract 3 (sum) from 6 or take 3 away from 6 or 6-3=3
theh subtract 3, 3-3=0
so
-(2+1)+6-3 or 6-(2+1)-3=0
the sum of 2 and 1 is 3
then you subtract 3 (sum) from 6 or take 3 away from 6 or 6-3=3
theh subtract 3, 3-3=0
so
-(2+1)+6-3 or 6-(2+1)-3=0
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.